Kolaborasi Pemerintah Kampung dengan Perusahaan Tapioka Dalam Mencegah Pencemaran Lingkungan Hasil Pengelolaan Singkong - M Fajar Novriansyah; Maulana Mukhlis; Pitojo Budiono; Ni Kadek Poniasih (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2021)
This article aims to find out the collaboration between the village government and tapioca companies in solving environmental pollution problems caused by cassava waste management. The problem is focused on the collaboration of the local government and tapioca companies in solving environmental problems resulting from drying the results of cassava management carried out by some people in Sangga Buana Village, Central Lampung Regency. In order to approach this problem, Ansel and Gash (2007) reference the theory of collaborative governance. The data were collected through interviews and analyzed qualitatively. The results in this study are drying the remaining cassava waste past the environmental quality stone limit. Pollutant elements in the environment pass the established environmental quality standards, so that the environment is polluted. There are two types of environmental quality stones that are affected by pollution, namely water quality standards and ambient air quality standards. The collaboration between the Village Government and the Tapioca Company has been going well, as evidenced by several indicators, namely face-to-face dialogue, building trust, commitment to the process, and sharing understanding. This study concludes that the collaboration process between the village government and the company is carried out quite well in accordance with the mutual understanding developed by both parties so that the tapioca company is committed to the agreement made.